Thinking outside the borders : library leadership in a world community - a manual for professional development (Mortenson Center for International Library Programs at the University of Illinois Urbana-ChampaignUS, 2008)
Focuses on developing strategies to meet the changing needs of patrons, including preservation, digitisation, acquisition of new or enhanced skills and resource sharing.
Collaboration of the Mortenson Center for International Library Programs and Illinois State Library. Project grant from the Institute of Museum and Library Services.